What Is the Price and Claimed Efficacy of Platelet-Rich Plasma Injections for the Treatment of Knee Osteoarthritis in the United States? - Piuzzi, Nicolas S.; Ng, Mitchell; Kantor, Ariel; Ng, Kenneth; Kha, Stephanie; Mont, Michael A.; Muschler, George F. (The Journal of Knee Surgery, 2019)
Platelet-rich plasma (PRP) injections are often used for the treatment of knee osteoarthritis (OA), despite clinical value and cost-effectiveness not being definitely established. PRP injections are considered as a potential means of reducing pain and improving function in patients with knee OA, in the hope of delaying or avoiding the need for surgical intervention. Centers that offer PRP injections usually charge patients out of pocket and directly market services. Therefore, the purpose of this study was to quantify the current (1) prices and (2) marketed clinical efficacy of autologous PRP injections for knee OA. A prospective cross-sectional study was performed based on 286 centers identified in the United States offering PRP injections for knee OA. A total of 179 (73.4%) centers were successfully contacted via e-mail or phone, using a simulated 52-year-old male patient with knee OA. Scripted questions were asked by the simulated patient to determine the current marketed prices and clinical efficacy, either reported as “good results” or “symptomatic improvement,” claimed by each treating center. The mean price for a single unilateral knee same-day PRP injection was $714 with a standard deviation of $144 (95% confidence interval [CI]: $691–737, n = 153). The mean claim of clinical efficacy was 76% with a standard deviation of 11% (95% CI: 73.5–78.3%, n = 84). Out of the 84 clinics, 10 claimed “90 to 100% efficacy,” 27 claimed “80 to 90%,” 29 claimed “70 to 80%,” 9 claimed “60 to 70%,” 8 claimed “50 to 60%,” and 1 claimed “40 to 60%.” These findings provide a unique perspective on the PRP market for the treatment of knee OA that is valuable to physicians and health care providers in providing better education to patients on the associated costs and purported clinical benefits of PRP injections.
Keywords: knee; osteoarthritis; biologics; platelet-rich plasma